1992
DOI: 10.1055/s-2007-994662
|View full text |Cite
|
Sign up to set email alerts
|

How Small is Too Small and How Early is Too Early? A Survey of American Obstetricians Specializing in High-Risk Pregnancies

Abstract: Four hundred and five Maternal-Fetal Medicine specialists were surveyed to determine their clinical opinions regarding intrapartum management of the severely preterm fetus requiring delivery. Intrapartum fetal heart rate monitoring was initiated at 23, 24, and 25 weeks' gestation by 10%, 43%, and 66% of respondents, respectively. Cesarean section was not performed at less than 24 weeks' gestation or less than 500 gm fetal weight. Ninety percent of respondents were willing to perform cesarean section for fetal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
1
6
0
2
Order By: Relevance
“…Nuthalapaty et al [13] conducted a survey of U.S. MFM providers and also found the perceived threshold of viability to be 23-24 weeks. Comparing these findings to a survey by Amon et al [14] in 1992, which found 26 weeks was a major threshold for intervention by cesarean delivery, supports recognition of the improvement in neonatal care occurring over the past two decades.…”
Section: Discussionsupporting
confidence: 73%
“…Nuthalapaty et al [13] conducted a survey of U.S. MFM providers and also found the perceived threshold of viability to be 23-24 weeks. Comparing these findings to a survey by Amon et al [14] in 1992, which found 26 weeks was a major threshold for intervention by cesarean delivery, supports recognition of the improvement in neonatal care occurring over the past two decades.…”
Section: Discussionsupporting
confidence: 73%
“…When the prognosis is poor, obstetricians often try to limit maternal morbidity by avoiding a cesarean section and allowing the infant to deliver naturally without active monitoring. [27][28][29] Data on obstetric decisions for mode of delivery, the presence or absence of a neonatologist, and the exact approach to resuscitation in the delivery room were not available. Also, information regarding subsequent withdrawal of intensive care on compassionate grounds was not available.…”
Section: Discussionmentioning
confidence: 99%
“…Several publications have attempted to define the best management in such situations 3,4,13 . The results of studies such as EPIPAGE will make it possible to assess the consequences of these early Cesarean sections both on mothers and on their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…The large number of publications on the subject reflects the extent and seriousness of the ethical questions faced by clinicians and by the scientific community as a whole about the management and outcome of the most preterm babies. However, these questions are raised mainly by obstetric-pediatric teams [1][2][3][4][5] or pediatricians [6][7][8][9][10][11][12] , and only rarely by obstetricians alone [13][14][15] . Nonetheless, decisions having important consequences for both child and family are made by obstetricians before or at delivery; better knowledge of the decision-making process is needed.…”
Section: Introductionmentioning
confidence: 99%